2016
DOI: 10.1111/bjh.14038
|View full text |Cite
|
Sign up to set email alerts
|

Increased microcirculation detected by dynamic contrast‐enhanced magnetic resonance imaging is of prognostic significance in asymptomatic myeloma

Abstract: This prospective study aimed to investigate the prognostic significance of dynamic contrast enhanced magnetic resonance imaging (DCE-MRI) as a non-invasive imaging technique delivering the quantitative parameters amplitude A (reflecting blood volume) and exchange rate constant kep (reflecting vascular permeability) in patients with asymptomatic monoclonal plasma cell diseases. We analysed DCE-MRI parameters in 33 healthy controls and 148 patients with monoclonal gammopathy of undetermined significance (MGUS) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 43 publications
(52 reference statements)
0
13
0
Order By: Relevance
“…Pearson correlations were calculated with the cor.test package in R and correlation plots were prepared with ggpubr and corrplot packages in R. For correlations only p values < 0.0001 were considered statistically significant, and the strength of the correlation was described as follows: 0.00-0.19 "very weak", 0.20-0.39 "weak", 0.40-0.59 "moderate", 0.60-0.79 "strong", 0.80-1.0 "very strong" [94]. Kaplan-Meier and Cox regression analyses were performed and visualized using the survival and survminer packages in R. The optimal cutpoint for these analyses was generated by the function "surv_cutpoint" which originates in the "maxstat" R package [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…Pearson correlations were calculated with the cor.test package in R and correlation plots were prepared with ggpubr and corrplot packages in R. For correlations only p values < 0.0001 were considered statistically significant, and the strength of the correlation was described as follows: 0.00-0.19 "very weak", 0.20-0.39 "weak", 0.40-0.59 "moderate", 0.60-0.79 "strong", 0.80-1.0 "very strong" [94]. Kaplan-Meier and Cox regression analyses were performed and visualized using the survival and survminer packages in R. The optimal cutpoint for these analyses was generated by the function "surv_cutpoint" which originates in the "maxstat" R package [95,96].…”
Section: Discussionmentioning
confidence: 99%
“…It has the advantage of evaluating a large volume of the bone marrow, overcoming the sampling bias of trephine biopsies. 2 For DCE-MRI in myeloma patients, a fat-suppressed T 1 weighted ultrafast gradient echo sequence of the thoracolumbar or lumbar spine (more rarely of the pelvis) is usually acquired. Semi-quantitative perfusion parameters can be extracted from TICs, by drawing ROIs.…”
Section: Whole Body Mri and Whole Body Diffusionweighted Imagingmentioning
confidence: 99%
“…Diffusion-weighted imaging (DWI) and dynamic contrast enhanced (DCE) MRI permit noninvasive evaluation of tumor-specific characteristics related to cellularity and angiogenesis and can thus improve diagnosis, prognostication, treatment planning and response assessment. [1][2][3] Both diffusion and perfusion quantification can be provided from intravoxel incoherent motion (IVIM) modelling. 4 Whole body MRI (WBMRI) has been recently recommended as a first line imaging modality by the International Myeloma Working Group.…”
Section: Introductionmentioning
confidence: 99%
“…MRI has proven to be a suitable tool for risk stratification of SMM patients, using abnormal bone marrow pattern [ 7 , 8 ], count of FLs [ 5 , 6 , 9 , 10 ], development of MRI findings [ 6 ] or even parameters from dynamic contrast enhancement MRI (DCE-MRI) as criteria to isolate high-risk groups [ 11 ]. Additionally, it was shown that volumetry is the superior method of quantifying tumor burden [ 12 , 13 ] and that volumetry can contribute to proper risk stratification in lung cancer screening [ 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%